PENENTUAN INDEKS dan KOEFISIEN LAJU GERMINASI KEDELAI (Glycine max (L.) Merr) yang DIBERI PENGASAPAN (Liquid Smoke) dari SUMBER MATERIAL TUMBUHAN yang BERBEDA - Wahyu Dani Swari; Basry Yadi Tang; Stormy Vertygo (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2021)
The research aimed at determining the Germination Rate Index (ILG) and Coefficient Velocity of Germination (KLG) of Soybean treated with liquid smoke derived from different plant materials. The seeds were soaked with liquid smoke from 3 different plant sources: Kesambi wood, coconut shell, and rice husk with each source were then divided into six variety of concentration: 0%, 10%, 20%, 30%, 40% and 100%. Analysis was conducted by calculating the GRI and CVG based on the parameters observed which were : Germination Time (GT) and Mean Germination Time (MGT). Results showed that liquid smoke derived from Kesambi wood gave the best result in promoting Soybean germination. Based on its ILG and KLG value . Results showed that liquid smoke derived from Kesambi wood gave the best result in promoting Soybean germination. Based on its ILG and KLG value, Kesambi wood-derived liquid smoke with 10% concentration gave the best value which were 50,00 and 2,00 respectively. On the other hand, liquid smoke derived from coconut shell and rice husk inhibited Soybean germination starting from 10% concentration. It is suggested to use liquid smoke derived from Kesambi wood to promote seed germination with lower concentration.